2014
DOI: 10.4236/nm.2014.51009
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, Psychopathology and Alcohol Misuse in Adolescence: A Population Based Study on 3556 Teenagers

Abstract: Objectives: To analyze the association between alexithymia and alcohol intake during adolescence, also in relation to psychopathology, in order to identify psychological risk factors for alcohol misuse. Method: 3556 students [mean age (range) 14.5 years (11 -18)] were recruited in the Padua area. Each was administered a set of three questionnaires: the Toronto Alexithymia Scale for children (TAS-20) to measure alexithymia, the Questionnaire Adolescent Saturday evening (QAS) to estimate of alcohol intake, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
5
13
0
1
Order By: Relevance
“…It is generally agreed that some models of alcohol consumption, and particularly those associated with a rapid ingestion and intoxication (like binge drinking), are systematically accompanied by physical and psychological damage, and social and behavioral issues (3)(4)(5)(6)(7)19). This was confirmed by the present study, which revealed that mean levels of internalizing, externalizing and total problems increased with larger amounts of alcohol being consumed during a given drinking episode.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is generally agreed that some models of alcohol consumption, and particularly those associated with a rapid ingestion and intoxication (like binge drinking), are systematically accompanied by physical and psychological damage, and social and behavioral issues (3)(4)(5)(6)(7)19). This was confirmed by the present study, which revealed that mean levels of internalizing, externalizing and total problems increased with larger amounts of alcohol being consumed during a given drinking episode.…”
Section: Discussionsupporting
confidence: 80%
“…Adolescents are particularly vulnerable, due to rapid and significant psycho-physical changes, they could experience sensations such as discomfort, inadequacy or confusion. These feelings may cause the use of attractive altering substances as regulators (2)(3)(4)(5). The consequences for adolescent "binge drinkers" are numerous, including neurobiological and organic damage, and possibly even severe alterations to the respective cognitive, emotional, behavioral and psychic functional correlates.…”
Section: Introductionmentioning
confidence: 99%
“…These opposing forces impacting emotion conceptualization across age (i.e., increasing verbal abilities vs. decreasing ease at identifying emotional states) could generate either increased or decreased emotional awareness. In fact, studies on the development of emotional awareness have produced inconsistent results: Some studies show increased emotional awareness across ages 11-18 (Gatta et al, 2014;Säkkinen, Kaltiala-Heino, Ranta, Haataja, & Joukamaa, 2007), but others find decreased emotional awareness with pubertal development (van der Cruijsen, Murphy, & Bird, 2019). If emotional awareness decreases during the transition to adolescence, it might be one factor explaining the well-established increase in risk for psychopathology that emerges transdiagnostically during this period (Kessler et al, 2005).…”
mentioning
confidence: 99%
“…Alexithymia was established as a personality construct in the early 1970s, typified by difficulty in identifying and describing emotions and externally oriented thinking (Sifneos, 1973). The prevalence rate is around 10% of the general population (Mattila, Salminen, Nummi & Joukamaa, 2006) with some European studies finding up to 23% (Gatta et al, 2014). As Alexithymia is characterised by the inability to express emotion, it is consequently associated with a range of somatic and psychiatric issues such as anxiety (Karukivi et al, 2010), depression (Honkalampi et al, 2000), substance abuse disorders (Ghalehban & Besharat, 2011) and problematic alcohol use (Thorberg et al, 2011).…”
mentioning
confidence: 99%